“Na hora que eu tomo, eu sei que aquilo é bom. Desse tamanhozinho, mas faz um estraaago!”: a experiência de ambiguidade com o uso da hormonioterapia no combate ao câncer de mama. - Marianna Cardoso de Araújo Souza (2024)
Breast cancer represents a heterogeneous set of diseases caused by the progressive accumulation of mutations that originate in the mammary glands. Hormone therapy plays a fundamental role in pharmacological treatment as it reduces the risk of recurrence and mortality in patients whose tumor is of the hormone-dependent type. The medication experience from the perspective of its user constitutes a multidimensional phenomenon, capable of influencing the pharmacotherapeutic decision-making process and, therefore, interfering in its subsequent clinical outcome. This study aimed to reveal the subjective experience of patients with breast cancer using hormone therapy associated with daily medication use. This is qualitative research in the light of Max van Manen's Phenomenology of Practice, whose operationalization provides a methodical framework capable of accessing a deep understanding of the human experience and respective individual and/or collective meanings for people's lives. Women over eighteen years of age were invited to participate in the study; diagnosed with breast cancer; who were using hormone therapy for this condition for a period equal to and/or longer than one year; and who were undergoing one or more pharmacological treatments concomitant to oncological therapy. The methodological instruments used were individual interviews, carried out from July to September 2023, which were recorded and later transcribed; notes in a field diary during and after the interviews; and observation. As a result, three themes emerged from the interviews. The first theme is called “The structures of subjective experience with the use of hormone therapy in the treatment of breast cancer”, which branched into three consecutive subthemes: (i) “‘Collapse. It’s just what you are’: the experience of corporeality”; (ii) “‘We have to have support from people, because we can’t live this life alone’: the experience of sociability”; and (iii) “‘You think it’s good, because you have the medicine and, at the same time, you think it’s bad, because it’s a looooong treatment’: the experience of temporality”. The second theme is configured by the title “‘I haven’t been taking this medicine for a month, two months. It has to fit into my routine’: pharmacotherapy and life management”; followed by the third theme, “‘The others (medications), I know I have to take. Anastrozole, I’m afraid of forgetting!’: hormone therapy and concomitant medications for chronic use, a comparative relationship”. Ambiguity constituted the essence of the phenomenon investigated, as well as being linear in the time continuum. The experience, in vogue, with the daily use of medicines revealed to be a socially constructed experience, which involves a multifaceted interrelationship between personal, social and structural factors, the burden of which women attribute to each of the components, hormone therapy and non-oncological medications is not uniform. The data obtained offer important contributions at theoretical, social and practical levels. Understanding this subjective experience, from the point of view of the individual's global pharmacotherapy, allows the pharmacist to identify, prevent and resolve problems related to the use of this therapeutic tool, which translates into greater effectiveness of interventions and an increase in the quality of life of the subjects. In addition, it provides support for the reorientation of approaches to current pharmaceutical clinical practice and consecutive collaboration to improve health care and, in particular, oncology.